Biomarkers in bipolars disorders - Machado-Vieira , Rodrigo; Soares, Jair C. (Academic Press, 2022)
Biomarkers in Bipolar Disorders summarizes cutting-edge findings in biomarkers' research, emphasizing the most promising findings, tools and technologies relevant to drug development and personalized medicine. Key findings cover different levels of evidence such as genes, molecules, cells, systems, brain and behavior related to diagnosis (state and trait/endophenotypes), prediction of treatment response and follow-up outcomes, along with the most promising perspectives in each area. Each section includes a comprehensive and focused overview on the state-of-the-art and perspectives. The book concludes with a section on practical applications, encompassing diagnostics development (genetic testing, biomarkers), and new drug development.